Implementation of a Performance Evaluation Policy for Regional Police Metro Jaya Employees Using an Online Performance Management System - Frihamdeni Frihamdeni; I Made Suwandi (Journal of Public Administration and Government, 2022)
The National Police has used information technology to manage its personnel's performance appraisals through an online Performance Management System (PMS) that can be accessed via the website and apps that can be downloaded for free on smartphones. The online PMS policy is implemented to increase the objectivity of Polri personnel in developing their careers. The author raises issues concerning the implementation of the Regional Police Metro Jaya online PMS policy and the factors that influence its implementation. The author will analyze the issues raised using Edward III's policy implementation concept and Williams' performance management system. The author conducts a study of documentation, observation, and in-depth interviews in this study, which employs a qualitative approach with a descriptive analytical research type. According to the findings, the Metro Jaya Regional Police followed up on organizational policies by placing online PMS operators in each work unit to manage and supervise policy implementation. Prior to implementation, the appointed operators were socialized regarding the online PMS policy. Furthermore, in order to save time and space for these operators, all personnel in their respective work units were socialized once more. The policy is socialized both formally and informally among personnel using social media. However, from the beginning of the implementation in early 2019, until now, it has decreased and is inconsistent in inputting performance appraisal data by each work unit, so that the attitude of the performance appraisal implementers is still less responsive. Another barrier to data entry is that the online PMS application is only available on the Android operating system and is still in the development stage, which can interfere with the data input process. It is hoped that the online PMS will make it easier for leaders to monitor and analyze their personnel's performance, as well as for members who are considered to be able to know the performance targets and performance achievements that have been carried out in order to motivate them to improve their performance in order to advance in their careers.